Сatalytic Phosphorylation of Aromatic C-H Bonds: from Traditional Approaches to Electrochemistry - Strekalova, Sofia; Khrizanforov, Mikhail; Sinyashin, Oleg; Budnikova, Yulia (Current Organic Chemistry, 2019)
The interest in organophosphorus compounds with a C-P bond is due to their wide use in various fields, especially in medicine and agrochemistry. Prominent examples of anti-cancer, antibacterial, and anti-HIV agents are therapeutic candidates containing a phosphonic acid group fragment. This review provides modern synthetic methods for obtaining phosphorylated aromatic and heteroaromatic compounds with the participation of complexes and salts of various metals developed in recent years as well modern protocol - electrochemical synthesis which allows carrying out reactions at room temperature and normal pressure with no additional oxidants or bases. Herein, we demonstrate new trends and evolution of phosphorylation reactions in catalysis.
Keywords: catalysis